The professional competence of the internal auditor and its impact on limiting creative accounting practices - Ali Kazem, Sumaya; Mohammed Ali Wahhab, Asaad (Iraqi Journal for Administrative Sciences, 2022)
The research aims to identify the role of the internal auditor in limiting creative accounting, measure the impact of the scientific and practical efficiency of the internal auditor, and draw the attention of internal auditors by seeking to develop their scientific and practical competence to meet the challenges of creative accounting and fraud. To achieve this goal, a questionnaire was designed as a tool for collecting data from the study sample consisting of 120 questionnaires on the sample members in the Iraqi companies listed on the Iraqi Stock Exchange, and 100 questionnaires were retrieved valid for analysis, the results of which were adopted for statistical analysis. The statistical programs SPSS were used, and Amos program and appropriate statistical methods in testing hypotheses and reaching a conclusion that the internal auditors’ possession of professional and academic certificates, their skills and knowledge of the field of accounting, economics and technology, and their participation in training courses in the field of accounting and internal auditing at least once a year, and their commitment to the rules and conduct of the profession all enhance the Based on the previous conclusions, the study recommends raising the awareness of internal auditors in the field of accounting and auditing through the introduction of specialized courses to reveal the motives and practices of creative accounting and how to reduce them